Robotic Transperitoneal Infrarenal Aortic Lymphadenectomy: Technique and Results. Issue 1 (1st January 2010) - Magrina, Javier F.; Long, Jaime B.; Kho, Rosanne M.; Giles, Dobie L.; Montero, Regina P.; Magtibay, Paul M.
Abstract : Introduction: This study was designed to evaluate the feasibility and the results of robotic transperitoneal infrarenal aortic lymphadenectomy. Methods: Development of a technique of robotic transperitoneal infrarenal aortic lymphadenectomy in female cadavers and review of the results in 33 patients who underwent the newly developed technique as part of the surgical treatment of gynecologic malignancies. Results: The mean console time was 42 minutes (range, 19-64 minutes). The mean number of nodes was 12.9 (range, 2-27); the mean number of positive nodes was 2.6 (range, 0-8). There was 1 conversion to laparotomy. Conclusions: Robotic transperitoneal infrarenal aortic lymphadenectomy can be performed adequately and safely with the robotic column at the patient's head. Operating table rotation and additional trocar sites are needed when used in conjunction with robotic pelvic surgery.